2019
DOI: 10.7883/yoken.jjid.2018.314
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Antibodies against Diphtheria, Tetanus, Pertussis, and Poliovirus Types I, II, and III Following Immunization with DTaP Combined with Inactivated Wild-Type Polio Vaccine (DTaP-wIPV)

Abstract: A follow-up serological study was conducted involving 47 subjects who received 4 doses of diphtheria and tetanus toxoids, combined with the acellular pertussis vaccine (DTaP) together with Salk-type inactivated polio vaccine (DTaP-wIPV), until 6 years of age. All antibody levels declined more rapidly than expected within 3 years after the completion of primary vaccination with the 4th booster dose, and titers persisted until 6 years of age. The positive rate of the IgG antibody against pertussis toxin (PT) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…(Swart et al 2016) Another longitudinal study following up the same individuals for seven years showed a biphasic waning pattern of anti-diphtheria toxoid IgG. (Nakayama et al 2019) The exponential decay model may not best fit, especially when follow-up time is longer.…”
Section: Discussionmentioning
confidence: 99%
“…(Swart et al 2016) Another longitudinal study following up the same individuals for seven years showed a biphasic waning pattern of anti-diphtheria toxoid IgG. (Nakayama et al 2019) The exponential decay model may not best fit, especially when follow-up time is longer.…”
Section: Discussionmentioning
confidence: 99%